Optimalisasi Tumbuh Kembang pada Balita dengan Smartpunturdi Desa Nyatnyono Kecamatan Ungaran Barat - Heny Romdiyani; Feronika Askini Mirino; Elsa Umi Anisa; Intan Agustina Sukmajaya; Yulia Nur Khayati (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2025)
The toddler period is known as the golden age of child development, which significantly determines intelligence, personality, and social skills in later life. However, many children in Indonesia still experience developmental delays due to a lack of early stimulation. One alternative, effective, and safe stimulation method is the Smartpunktur technique, a non-invasive reflexology massage that can be performed by parents at home. This community service activity aimed to improve mothers' knowledge of child growth and development, as well as their skills in practicing the Smartpunktur massage technique as an early stimulation effort. The activity was conducted on June 10, 2025, in Nyatnyono Village, Ungaran Barat District, Semarang Regency, involving 14 mothers of toddlers. The implementation methods included health education, demonstrations, discussions, hands-on practice, pre-test, and post-test. Educational media used were PowerPoint presentations and instructional videos. The pre-test showed that most participants had a moderate level of knowledge (64.5%) and only 7% fell into the good category. After the educational session and demonstration, there was a significant increase in knowledge, with 85.7% of mothers reaching the good category and no participants remaining in the poor category. The activity was well-received, with active participation from all attendees. Health education and Smartpunktur training effectively increased mothers’ knowledge about early childhood growth and development stimulation. It is recommended that similar training be conducted regularly at Posyandu and be supported by cadres and local health authorities.   Abstrak Masa balita merupakan periode emas perkembangan anak yang sangat menentukan kecerdasan, kepribadian, dan kemampuan sosial di masa mendatang. Namun, masih banyak anak di Indonesia mengalami hambatan perkembangan akibat kurangnya stimulasi dini. Salah satu metode stimulasi alternatif yang efektif dan aman adalah teknik Smartpunktur, yaitu pijat pada titik refleksi tertentu tanpa jarum, yang dapat dilakukan oleh orang tua di rumah. Kegiatan ini bertujuan untuk meningkatkan pengetahuan ibu balita tentang tumbuh kembang anak serta keterampilan melakukan teknik pijat Smartpunktur sebagai bentuk stimulasi dini. Kegiatan pengabdian masyarakat dilakukan pada 10 Juni 2025 di Desa Nyatnyono, Kecamatan Ungaran Barat, Kabupaten Semarang, melibatkan 14 ibu balita. Metode pelaksanaan meliputi penyuluhan, demonstrasi, diskusi, praktik langsung, pre-test dan post-test. Media yang digunakan berupa PowerPoint dan video edukasi. Hasil pre-test menunjukkan mayoritas ibu memiliki pengetahuan cukup (64,5%) dan hanya 7% dalam kategori baik. Setelah penyuluhan dan demonstrasi, pengetahuan meningkat signifikan, dengan 85,7% ibu masuk kategori baik dan tidak ada peserta di kategori kurang. Selain itu, kegiatan berjalan lancar dengan partisipasi aktif seluruh peserta. Penyuluhan dan pelatihan teknik Smartpunktur efektif meningkatkan pengetahuan ibu balita tentang stimulasi tumbuh kembang. Disarankan agar pelatihan serupa dilakukan secara rutin di Posyandu dan didukung pendampingan kader serta Dinas Kesehatan setempat.